I have to solve the following equation

$$ z'-e^z=2$$

where $z=f(x)$, but I can't solve this. Could you please help me ?

up vote 8 down vote accepted

Try multiplying by $\mathrm{e}^{-z}$, as this will lead to $$ \mathrm{e}^{-z}z’ - 1 = 2\mathrm{e}^{-z} $$ Or $$ -(\mathrm{e}^{-z})’ - 1 = 2\mathrm{e}^{-z} $$ We can then re-write as $$ -y’ -1 = 2y $$ With $y=\mathrm{e}^{-z}$. Should be easier to solve.

it looks like Bernouilli 's equation $$z'=e^z+2$$ substitute $$u=e^z+2 \implies \frac {du}{dz}=e^z=u-2$$ The equation becomes $$\frac {dz}{dt}=u$$ $$\frac {dz}{du}\frac {du}{dt}=u$$ $$\frac {du}{dt}=u\frac {du}{dz}$$ $$\frac {du}{dt}=u(u-2)$$ $$u'_t+2u=u^2$$ This last one is Bernouilli's equation. But it's also separable. And easier to integrate that way $$\int \frac {du}{u(u-2)}=\int dt$$

Your Answer

 

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.